KEDUDUKAN WALI NIKAH MENURUT SHAMSI ALI (STUDI KOMPARATIF ANTARA MAZHAB HANAFI DAN MAZHAB SYAFI’I) - Hamzah H. (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2022)
This research is about the Position Position of Marriage Guardian according to Shamsi Ali (A Comparative Study between the Ḥanafi and Syāfi‘i school) This research is a literature study using (a) munakahat fiqh approach (b )historical approach (c) anthropological approach (d) normative theological approach (e)philosophical approach. The results of this study indicate that the position of the guardian of marriage according to the Ḥanafi school is not a pillar of marriage, Ḥanafi school allows the bride to pronounce her own consent, on condition that the bride must be mature, intelligent and in agreement with her future husband. The existence of a guardian in marriage according to the Ḥanafi school is not obligatory, but only perfect. The Syafi'i school considers the batil marriage contract whose ijab statement is pronounced by a woman, either a girl or a widow, sekufu or not, directly for herself or as a representative for others. Shamsi Ali considers marriage legal if the bride pronounces her own consent, the guardian only needs to give permission, Shamsi Ali reasons that, it will be much better and deeper in meaning if the bride directly recites her own consent because of the direct involvement of the bride and groom. Shamsi Ali also emphasized that, indeed, there is no verse that explicitly indicates that a guardian must pronounce consent for marriage.